Light guiding properties of negative-curvature hollow-core fiber - Wang, Yuxi (Nanyang Technological University, 2022)
Negative curvature hollow-core fibers have become increasingly attractive as an excellent waveguide platform. Negative curvature fibers have exceptional optical properties, such as high optical damage threshold, low nonlinearity, and tunable dispersion, which make them promising for various applications,such as high power beam delivery, telecommunications, and gas-based nonlinear optics. In negative curvature fibers, the presence of the negative curvature at the core-cladding interface, as well as the absence of the nodes between the adjacent cladding element are two crucial structural features that have large impact on the light guidance. Presently, the most widely used family of negative curvature fibers is the single ring negative curvature fiber, where a single ring of dielectric cladding tubes surround the central hollow region. Another successful type is the nested antiresonant nodeless hollow core fiber, which have shown remarkably low transmission loss of 0.22 dB/km. The thesis focuses on the investigation on the light guiding properties of negative-curvature hollow-core fibers. First, we presented a comprehensive numerical investigation on the effect of introducing outer cladding tubes on the guiding properties in double-ring negative-curvature fiber. We determined the range of geometrical parameters, which exhibited the best guiding properties in the double-ring geometry. Our study showed that introducing an outer cladding tube can reduce the confinement loss by up to four orders of magnitude in negative-curvature hollow-core fiber. Bending and modal properties can also be improved. We found that the low-loss region can be shifted by varying the thickness of outer cladding tubes, indicating the loss reduction derived from the enhanced anti-resonant reflections provided by the interface of outer cladding tubes. We carried out a thorough numerical analysis on the bending-induced loss in negative-curvature hollow-core fibers. The result shows that varying structural parameters change the bending performance via altering the resonant coupling and other bending-induced effects. We provided the underlying mechanism on how resonant coupling and other bending-related phenomena influence the bending properties of negative curvature fiber. From this analysis, we identified the structural parameters for achieving light guidance with low bending sensitivity. Our numerical results also show that higher-order modes can be effectively suppressed through the mechanical bending of the fiber. We fabricated several types of single-ring negative curvature fibers. They have exhibited excellentvii light-guiding properties, featuring broadband and low-loss guidance. A seven-tube single-ring negative curvature fiber has demonstrated low-bend sensitivity light guidance in the two-micro region. The fiber can be useful for high power beam delivery and gas-based nonlinear optics. We fabricated and characterized a double ring negative-curvature fiber with a geometrical arrangement identical to that studied in our numerical study. The fiber exhibits superior loss performance than its idealized single ring counterpart, demonstrating its potential as a low-loss waveguide. Our results laid a good foundation for fabricating various double-ring negative-curvature fiber for achieving excellent guiding properties.